2020
DOI: 10.3390/biology9020026
|View full text |Cite
|
Sign up to set email alerts
|

Determining Ancestry between Rodent- and Human-Derived Virus Sequences in Endemic Foci: Towards a More Integral Molecular Epidemiology of Lassa Fever within West Africa

Abstract: Lassa fever is a viral hemorrhagic illness responsible for thousands of human deaths in West Africa yearly. Rodents are known as natural reservoirs of the causative Lassa mammarenavirus (LASV) while humans are regarded as incidental, spill-over hosts. Analysis of genetic sequences continues to add to our understanding of the evolutionary history, emergence patterns, and the epidemiology of LASV. Hitherto, the source of data in such investigations has mainly comprised human clinical samples. Presently, a rise i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 32 publications
4
15
0
1
Order By: Relevance
“…On the other hand, this study showed that certain pygmy mice, Mus baoulei, circulating in the fields around the houses were carriers of the LASV virus belonging to the same cluster as the Beninese strains, but genetically very distant. This is specific to this new lineage, because when humans are infected with strains circulating in rodents in their environment, phylogenetic analysis shows some trees with very close "rodent" branches and "human" branches [35][36][37]. For example, the GP-LASV sequences observed in M. natalensis and Homo sapiens living in the Ekpoma zone of Nigeria showed an amino-acid similarity of approximately 95-99% [36], whereas we observed a similarity of approximately 90-92%.…”
Section: Discussionmentioning
confidence: 60%
“…On the other hand, this study showed that certain pygmy mice, Mus baoulei, circulating in the fields around the houses were carriers of the LASV virus belonging to the same cluster as the Beninese strains, but genetically very distant. This is specific to this new lineage, because when humans are infected with strains circulating in rodents in their environment, phylogenetic analysis shows some trees with very close "rodent" branches and "human" branches [35][36][37]. For example, the GP-LASV sequences observed in M. natalensis and Homo sapiens living in the Ekpoma zone of Nigeria showed an amino-acid similarity of approximately 95-99% [36], whereas we observed a similarity of approximately 90-92%.…”
Section: Discussionmentioning
confidence: 60%
“…While a LASV vaccine is still unavailable, increasing insight into LF ecology, particularly where LASV rodent hosts are concerned, can provide a more dependable assessment of zoonotic risk. In this regard molecular analysis as a tool has proven useful, driving a series of advances in the mapping of LASV occurrence, lineage clustering and more accurate identification of rodent hosts [ 35 ]. Most of the findings so far have enabled virus and rodent genetic categorisation across the West African region at the ‘lineage’ level.…”
Section: Discussionmentioning
confidence: 99%
“…1 ) should aim to link human and rodent data more directly at a finer scale. They also recommended that longitudinal sampling regimes be supported by opportunistic rodent screening at home addresses where humans test LASV-positive [ 35 ].…”
Section: Rodent Dynamics and Lassa Fever Outbreaksmentioning
confidence: 99%
“…In Guinea, numerous LASV sequences have been largely described in rodents, notably in the region of Faranah (221 sequences), Kindia (6 sequences) and Guékedou (9 sequences) [ 9 , 10 , 11 , 20 , 21 ]. However, only 5 sequences are derived from humans, 2 complete from Faranah and Macenta [ 22 , 23 ], and 3 partials from Kissidougou and Nzérékoré [ 14 ].…”
Section: Discussionmentioning
confidence: 99%